“It's the black girls that have the most”: foodways narratives and the construction of race in a women's prison - Smoyer, Amy B (Food and Foodways, 2015)
Prison foodways narratives can expand knowledge about cultural beliefs and perceptions of correctional systems. This exploratory analysis, based in qualitative interview data, seeks to initiate dialogue about the ways in which formerly incarcerated women in the US deploy racialized food narratives when describing the acquisition, preparation, and consumption of prison food. The participants’ food narratives construct prison as a non-white space that is better matched for African-American and Latina women, reinforcing and enacting larger cultural notions about incarceration. This opening analysis calls for more research and deliberation about how prison foodways narratives contribute to understandings about and perceptions of correctional systems and incarcerated people. © 2015, Taylor & Francis Group, LLC.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/076-302-356-756-556 tex.type: [object Object]
Keywords: dept.swk